Mouse skin-derived precursors alleviates ultraviolet B irradiation damage via early activation of TGF-β/Smad pathway by thrombospondin1 - Li, Yiming (Cell Cycle, 2020)
Our previous research implied mouse skin-derived precursors (mSKPs) possessed the capacity of anti-ultraviolet B (UVB) irradiation damage, and the mechanisms might be associated with transforming growth factor-β (TGF-β) signaling pathway activation. In this study, we investigated and compared the response to UVB irradiation between mSKPs and dermal mesenchymal stem cells (dMSCs), and explored the underlying mechanisms. Irradiation damage such as decreased cell viability, cell senescence, and cell death was observed in both mSKPs and dMSCs at 24 h after UVB exposure. In mSKPs, change in cell morphology, viability, cell senescence and death at the following time points implied the recovery of UVB irradiation damage. Additionally, thrombospondin1 (TSP1) and TGF-β1 increased significantly in mSKPs’ supernatant after UVB irradiation. The gene expression of TSP1, TGF-β1, metalloproteinase 1 (MMP1), and Collagen I elevated shortly after the UVB exposure. The protein expression of TSP1, TGF-β1, MMP1, Collagen I, smad2/3, and p-smad2/3 at multiple time points after the UVB exposure was consistent with the gene expression results. In dMSCs, no obvious recovery was noticed. Together, these results revealed that in mSKPs, one of the mechanisms to attenuate the UVB irradiation damage might be the early activation of TGF-β/Smad pathway by TSP1. Given that mSKPs could differentiate into fibroblast-like SKP-derived fibroblasts (SFBs) in vivo or with the presence of serum, mSKPs might serve as a therapeutic potential for fibroblasts supplement and UVB irradiation damage treatment. Abbreviations: SKPs: skin-derived precursors; mSKPs: mouse SKPs; UVB: ultraviolet B; TGF-β/Smad: transforming growth factor-β/Smad; TSP1: thrombospondin 1; MMP 13: metalloproteinases 13; TβRII: TGF-β receptor II; SFBs: SKP-derived fibroblasts; KEGG: Kyoto encyclopedia of genes and genomes; DEGs: differentially expressed genes; dMSCs: dermal mesenchymal stem cells; LM: light microscope; CCK-8: cell counting kit 8; ELISA: Enzyme-linked immuno sorbent assay; qRT-PCR: quantitative real-time polymerase chain reaction; TSPs: thrombospondins; ECM: extracellular matrix; R-smads: receptor-regulated smads